Sosialisasi Pembelajaran Daring Pada Kegiatan Belajar Mengajar - Hasanah, Uswatun; Qomariyah, Ryzca Siti (Abdi Panca Marga, 2023)
This sosialization aims to see how the process of online learning activities that take place in the field and the efforts that can be made to make the online learning process run better. The aim of the researcher is to disseminate information regarding online learning to teaching and learning and whether there are effective ways that can be taken if there are obstacles in this online learning. The method used is to describe the methods used to solve problems or obstacles in online learning, including: methods a) Community Education, namely counseling or socialization that aims to provide understanding and awareness to parents (community) of the importance of online learning done at home. b) Training, namely skills in using technology both from the teacher, parents, and students require training on the technology that will be used during this online learning c) Advocacy, namely that students must be accompanied by parents/teachers in the use and use of the technology. The results of the method in solving these problems, the teacher is required to be able to design and design online learning that is light and effective, by utilizing the right devices or online media and in accordance with the material being taught. In its implementation, online learning requires the support of mobile devices such as smartphones or android phones, laptops, computers, and tablets, etc. that can be used to access information anytime and anywhere. The success of the teacher in conducting online learning is the teacher's ability to innovate in designing, and concocting materials, learning methods, and applications that are in accordance with the materials and methods. This is done by making a systematic, structured and simple schedule to facilitate communication between parents and the school so that their children studying at home can be monitored effectively. Thus, good cooperation between teachers, students, parents and the school/madrasah is a determining factor for more effective online learning. The implementation of learning is not without problems. However, there are obstacles in online learning, namely not all places have a good enough internet network/Network problems, lack of training, and lack of awareness are stated as the most important reasons by those who do not adopt online learning followed by lack of interest and doubts about the usefulness of online learning. Lack of presence, lack of personal touch, and lack of interaction due to connectivity issues were found to be significant drawbacks of online learning (Arora and Srinivasan, 2020). Solving problems/obstacles from the impact of online learning after holding public education (counseling), training, and advocacy results: parents of students become aware of the importance of accompanying their children in online learning during this covid-19 pandemic. Not only that, they (parents & students) have become more skilled in using technology with mobile devices that have been trained. The relationship between teachers, parents, and students goes well through collaboration during learning and assignments given by the teacher to students. The process of teaching and learning activities run effectively and efficiently because of the creativity of the teacher in designing learning.